KORELASI ANTARA PENGALAMAN MENGAJAR DENGAN KOMPETENSI PROFESIONAL GURU PAI DI MADRASAH ALIYAH NEGERI 3 PALEMBANG - Destri Rahayu; Akmal Hawi; Mardeli Mardeli; Sofyan Sofyan (PAI RAFAH, 2020)
The teacher is one of the dominant factors that is important in formal education. To improve the quality of education, one of the requirements is to improve the quality of educators, namely teachers. Teachers are part of a system that largely determines education. There are many things that improve a teacher's performance. One of them is teaching experience. With this teacher can have various kinds of skills, expertise and abilities needed in teaching and learning activities. Likewise, it will also be discussed with further education about teacher competencies. The time used by the teacher when teaching is still lacking in discipline, it can be seen that the compilation of class hours has begun, the teacher is still late in class. The purpose of this study was to study the relationship of teacher teaching experience with professional competence in Madrasah Aliyah Negeri 3 Palembang. This type of research is a type of quantitative research. Data collection techniques are done by questionnaire, and documentation. The questionnaire was used by researchers to see how the teaching experience and competence of professional teachers is. The data analysis technique in this study used a t-questionnaire to seek knowledge about teaching experiences with PAI professional teacher competencies in Madrasah Aliyah Negeri 3 Palembang or not. The results of this study are that there is a significant relationship between teaching experience with professional competence using the formula "product moment conversations" in Microsoft Excel, namely t-table 10.4157≥0.8597. Then the alternatives received in other words contained between the significance of teaching experience with PAI's professional competence at Madrasah Aliyah Negeri 3 Palembang.